Halogen‐Free On‐Surface Synthesis of Rylene‐Type Graphene Nanoribbons - Cai, Zeying; She, Limin; He, Yangyong; Wu, Liqin; Cai, Lang; Zhong, Dingyong (Macromolecular chemistry and physics, 2017)
Graphene nanoribbons (GNRs) are promising building blocks for nanoelectronic and spintronic devices. As a bottom‐up approach, on‐surface synthesis from predefined precursor molecules is widely applied for the fabrication of GNRs with precisely controlled edge structure and width. In order to guide the on‐surface reaction in a desired style, most of the chosen precursor molecules are functionalized with halogen atoms, while halogen‐free strategy for GNR synthesis is still challenging so far. Here, the on‐surface synthesis of ultranarrow armchair GNRs with five carbons across the ribbon (5‐aGNRs) on Au(111) surfaces via direct dehydrogenative CC coupling is reported. As the precursor molecule, quaterrylene molecules undergo various pathways of cyclodehydrogenation at submonolayer coverage: Instead of straight GNRs, a large proportion of the reaction products are kinked with an angle of 150°. When increasing the coverage to nearly one monolayer, the selectivity toward the straight GNRs is significantly enhanced. The coverage‐dependent reaction preference is ascribed to the intermolecular steric effect, in which the reaction pathway is constrained by the orientation of the neighboring molecules. Such an intermolecular steric effect is considered a novel approach to guide the on‐surface synthesis toward desired nanostructures. The on‐surface synthesis of rylene‐type grapheme nanoribbons (GNRs) on Au(111) surfaces via direct dehydrogenative CC coupling is reported. The quaterrylene molecules undergo various pathways of cyclodehydrogenation: At submonolayer coverage, predominant reaction products are kinked with an angle of 150°, while the selectivity toward the straight GNRs is significantly enhanced at one monolayer.